Can Indigenous and Community-Based Ecotourism Serve as a Catalyst for Land Sparing in Latin America?. (September 2021) - Gunter, Ulrich; Ceddia, M. Graziano
The present study investigates the role of ecotourism as a potential catalyst for land sparing in Latin America, with a particular focus on indigenous and community-based ecotourism. The research question is investigated within a comprehensive empirical land sparing–agricultural expansion framework, which uses the Jevons paradox as its theoretical foundation. It also allows for environmental governance and includes several socioeconomic control variables. In doing so, a panel data set based on secondary data from institutional sources and comprising 10 Latin American countries for the period from 1995 to 2015 is employed, which resulted in 209 observations in total. Panel estimation results show that there is only moderate evidence of land sparing associated with ecotourism, when it occurs on indigenous peoples' and local communities' land. To achieve land sparing through ecotourism, titling land to indigenous peoples and local communities as stakeholders is therefore crucial, but this beneficial effect should not be overestimated.